The Influence of Current Ratio and Sales Growth on ROA with WCT as a Mediating Variable in the FMCG Industry 2020 - 2024 - Dhea Olivia Putri; Maiyaliza Maiyaliza (Program Studi Keuangan & Perbankan, Fakultas Ekonomi dan Bisnis, Universitas Komputer Indonesia, 2026)
This study examines the influence of liquidity and sales growth on profitability, with working capital turnover as a mediating variable in Fast Moving Consumer Goods (FMCG) companies listed on the Indonesia Stock Exchange (IDX) for the period 2020 – 2024. A quantitative approach was employed using secondary data from annual financial reports. The research population consisted of 20 FMCG companies selected through purposive sampling, yielding a total of 100 samples. Data analysis utilized Strutural Equation Modelling (SEM) based on Partial Least Squares (PLS) via SmartPLS 4.0 software. The analysis result indicate that liquidity and sales growth have a significant positive effect on profitability. However, both variables don’t show a significant effect on working capital turnover. On the other hand, working capital turnover has a negative and significant effect on profitability. Furthermore, working capital turnover does not function as a mediator in the relationship between liquidity and sales performance on profitability. This research implies that FMCG companies need to maintain a balance between liquidity, sales growth, and working capital efficiency to enhance sustainable profitability. Keywords : Liquidity; Sales Growth; Working Capital Turnover; Profitability; FMCG